Radiographic Joint Damage And Reactants Of Acute Phase In Patients With Rheumatoid Arthritis - Dejan Spasovski; Sonja Genadieva Stavric; Tatjana Sotirova; Slavica Shubevska Stratrova (My University, 2020)
Objectives: Radiographic evaluation remains the most important tool for evaluation of the structural damage of joints and skeleton. Progression of the radiographic damage of hand and feet joints is a significant and objective variable for evaluation of disease activity as well as for measurement of treatment outcome. To compare the values of rheumatoid factor (RF), C-reactive protein (CRP) and DAS28 index in the early diagnosis of untreated rheumatoid arthritis (RA). Material and Methods: Using ELISA method DIA-STATTM Anti CCP (Axis–Shield Diagnostics), we tested sera of 70 participants (35 untreated RA, 35 control group). RF was determined with the agglutination test (Latex RF test) in the participants. Patients were treated with Methotrexate at an average dose of 10 mg once weekly. For clinical evaluation of disease activity in every patient radiographic index (RI), sedimentation, CRP and RF at certain time intervals (time 0, after 6, 9 and 12 months) were analyzed. Results: RA was evaluated by follow-up of the dynamics of the changes of mean values of RI score, mean values of sedimentation, CRP and RF. RI showed an increased radiographic progression of hand joint damage at time intervals between 0 and 9 months (p=0.0167) and between 0 and 12 months (p=0.0089). Statistical analysis showed statistically significant differences among mean values of ESR at four time intervals (p=0.00002). Also, statistically significant differences were shown in the mean values of CRP at four time intervals (p=0.0428) (standard deviations showed great variations). There were no statistically significant differences among mean values of RF at four time intervals (p=0.573). At time 0 in 3 (10%) patients (pts) RI progression was seen, after 6 months in 13 (39%), while after 9 and 12 months RI progression was seen in an equal number of patients 15 (50%). In most patients increased values of RF and CRP were registered. Conclusion: Progression of the radiographic damage continues, especially in patients with increased values of sedimentation, CRP and RF and persistence of previous hand joints erosions, as predictors of the aggressive course of disease. They enable selection of the high-risk groups for aggressive course of disease and indicate the need for early and aggressive treatment.
Keywords: rheumatoid arthritis; rheumatoid factor; reactants of the acute phase